Pelatihan Pemasaran Digital bagi UMKM Desa Sojomerto: Pendekatan Berbasis Kebutuhan Lokal - Kurniyah, Kurniyah; Satria, Bahtiar Raga; Mustaszar, Amir; Mubarok, Ahmad Mas’ul; Rodhiya, Ali Saidi; Wahyuni, santi; Mukaromah, Lailiya; hidayattullah, Nur Farid; Khumaedah, Isti; Wahid, Nur; Sarifah, Nadya Dian Noor; Anwaroh, Zumrotul; Amalia, Fikri; Satriani, Ayu; Laila, Miladia (LPPM Sekolah Tinggi Islam Kendal, 2026)
The rapid development of digital technology has created significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve their competitiveness and expand their market reach. However, many MSME actors have not yet optimally utilized digital marketing due to limited knowledge and skills. This community service activity aims to enhance the understanding and capabilities of MSME actors in digital marketing through a training seminar conducted by KKN Sojomerto 01 students. The methods employed include observation, training seminars, interactive discussions, and brief assistance. The results indicate an improvement in participants’ understanding of the use of social media and digital platforms as effective marketing tools. This activity is expected to encourage MSMEs to adapt to digital developments in order to increase sales and ensure business sustainability.